Analysis of CO2 storage efficiency and performance of low carbon cement binders containing carbide slag and phosphorus slag - Guang-Min Liu; Rui-Cong Gao; Fang Liu; Wen-Ping Yue; Yi Yang; Yong-Pang Liao; Jia-Xiang Liew (Journal of CO2 Utilization)
Phosphorus slag (PS) and carbide slag (CS) are waste residues generated in industrial production. Because PS and CS are not fully utilized, they have caused serious land occupation and resource waste. In this paper, PS and CS are used as auxiliary cementitious materials to study the modification mechanism of CS on PS and the synergistic mechanism of PS and CS in cement-based materials under different curing methods. First, CS can modify PS, weaken the retarding effect of phosphorus and fluorine elements remaining in PS on cement hydration, and promote the early hydration rate; secondly, CS can activate the volcanic ash activity of PS and reduce the adverse effects of the dilution effect. In addition, the generated hydration products can generate more SiO2-Al2O3 gel with a low calcium-silicon ratio after carbonation and decalcification. Finally, the carbonated specimen shows better high-temperature mechanical properties and volume stability than the normally cured specimen, and the high-temperature strength and specimens volume initially rise and subsequently decline as temperature rises.